Use of the Coupler Microanastomotic Device for the Treatment of a Distal Posterior Inferior Cerebellar Artery Aneurysm Via Excision and End-to-End Anastomosis—A Case Report. Issue 2 (29th May 2020) - Goren, Oded; Sampath, Raghuram; Patel, Akshal S; Griessenauer, Christoph J; Schirmer, Clemens M; Newell, David W
ABSTRACT: BACKGROUND AND IMPORTANCE: The Coupler microanastomotic device (Medical Companies Alliance, Birmingham, Alabama) aims at facilitating safe and efficient end-to-end reconstruction of the native vessel ends following resection of intracranial aneurysms. CLINICAL PRESENTATION: We report the first case of the Coupler device used to treat a ruptured posterior inferior cerebellar artery (PICA) aneurysm. Following aneurysmal trapping and excision, the native parent vessel ends were connected in an end-to-end fashion. CONCLUSION: The microanastomotic Coupler device is an acceptable option for end-to-end anastomosis and was successfully applied in the management of a ruptured fusiform PICA aneurysm.